STRATEGI KOMUNIKASI KUA DALAM MEMINIMALISIR PERNIKAHAN DINI DI KECAMATAN TAROWANG KABUPATEN JENEPONTO (Jurnal Washiyah: Jurnal Kajian Dakwah dah Komunikasi, 2024)
This thesis discusses the KUA's communication strategy for minimizing early marriage in Tarowang District, Jeneponto Regency. In this case, this research was conducted to determine the factors that cause early marriage in Tarowang District, Jeneponto Regency, and what forms of communication are implemented by the KUA in an effort to minimize early marriage in Tarowang District, Jeneponto Regency. This type of research is qualitative, using a communication approach and a sociological approach. The location of this research is in Tarowang District, Jeneponto Regency. Data was obtained through observation, interviews, and documentation. Data processing and data analysis techniques are carried out through four stages, namely data collection, data reduction, data presentation, and drawing conclusions. The results of this research are: First, the factors that cause early marriage in Tarowang District, Jeneponto Regency, include: 1) promiscuity, 2) economic factors, and 3) cultural factors, which play a role in the dynamics of marriage in the Tarowang District area. Second, the forms of communication implemented by the KUA in an effort to minimize early marriage in Tarowang District, Jeneponto Regency, namely 1) interpersonal forms of communication, which involve counseling, socialization, and direct assistance activities for individuals or groups; 2) organizational forms of communication, which include coordination and interaction within the KUA institution and with related parties; and 3) forms of mass communication, which involve conveying educational messages through online media and social media. The implication of this research is that the research results are expected to be the basis for developing more effective communication strategies for minimizing early marriage, and with this research, the people of Tarowang District can be more aware of the risks and consequences of early marriage and empower people in the area to contribute to minimizing early marriage. .